Prostaglandins in Superovulation Induced Bovine Follicles During the Preovulatory Period and Early Corpus Luteum - Berisha, Bajram; Rodler, Daniela; Schams, Dieter; Sinowatz, Fred; Pfaffl, Michael W. (Frontiers in Endocrinology, 2019)
The aim of this study was to characterize the regulation pattern of prostaglandin family members namely prostaglandin F2alpha (PTGF), prostaglandin E2 (PTGE), their receptors (PTGFR, PTGER2, PTGER4), cyclooxygenase 2 (COX-2), PTGF synthase (PTGFS), and PTGE synthase (PTGES) in the bovine follicles during preovulatory period and early corpus luteum (CL). Ovaries containing preovulatory follicles or CL were collected by transvaginal ovariectomy (n = 5 cows/group), and the follicles were classified: (I) before GnRH treatment; (II) 4 h after GnRH; (III) 10 h after GnRH; (IV) 20 h after GnRH; (V) 25 h after GnRH, and (VI) 60 h after GnRH (early CL). In these samples, the concentrations of progesterone (P4), estradiol (E2), PTGF and PTGE were investigated in the follicular fluid (FF) by validated EIA. Relative mRNA abundance of genes encoding for prostaglandin receptors (PTGFR, PTGER2, PTGER4), COX-2, PTGFS and PTGES were quantified by RT-qPCR. The localization of COX-2 and PTGES were investigated by established immunohistochemistry in fixed follicular and CL tissue samples. The high E2 concentration in the FF of the follicle group before GnRH treatment (495.8 ng/ml) and during luteinizing hormone (LH) surge (4 h after GnRH, 574.36 ng/ml), is followed by a significant (P<0.05) downregulation afterwards with the lowest level during ovulation (25 h after GnRH, 53.11 ng/ml). In contrast the concentration of P4 was very low before LH surge (50.64 mg/ml) followed by a significant upregulation (P < 0.05) during ovulation (537.18 ng/ml). The mRNA expression of COX-2 increased significantely (P < 0.05) 4 h after GnRH and again 20 h after GnRH, followed by a significant decrease (P < 0.05) after ovulation (early CL). The mRNA of PTGFS in follicles before GnRH was high followed by a continuous and significant downregulation (P < 0.05) afterwards. In contrast, PTGES mRNA abundance increased significantely (P < 0.05) in follicles 20 h after GnRH treatment and remained high afterwards. The mRNA abundance of PTGFR, PTGER2, and PTGER4 in follicles before GnRH was high, followed by a continuous and significant down regulation afterwards and significant increase (P < 0.05) only after ovulation (early CL). The low concentration of PTGF (0.04 ng/ml) and PTGE (0.15 ng/ml) in FF before GnRH, increased continuously in follicle groups before ovulation and displayed a further significant and dramatic increase (P < 0.05) around ovulation (101.01 ng/ml, respectively, 484.21 ng/ml). Immunohistochemically, the granulosa cells showed an intensive signal for COX-2 and PTGES in follicles during preovulation and in granulosa-luteal cells of the early CL. In conclusion, our results indicate that the examined bovine prostaglandin family members are involved in the local mechanisms regulating final follicle maturation and ovulation during the folliculo-luteal transition and CL formation.